Gender-Related Differences in Sickle Cell Disease in a Pediatric Cohort: A Single-Center Retrospective Study - Ceglie, Giulia; Di Mauro, Margherita; Tarissi De Jacobis, Isabella; de Gennaro, Francesca; Quaranta, Martina; Baronci, Carlo; Villani, Alberto; Palumbo, Giuseppe (Frontiers in Molecular Biosciences, 2019)
Sickle cell disease (SCD) is one of the most common monogenic disease worldwide. The incidence of SCD is not gender related since it is transmitted as an autosomal recessive disorder. We retrospectively analyzed the clinical records of 39 pediatric patients with a diagnosis of SCD (hemoglobin SS genotype) focusing on gender differences analyzing various aspects comprising both acute symptoms and late complications. We found various gender related differences in our pediatric population. Pain crisis frequency per year were significantly increased in the male population with a mean number of crisis per year of 1.6 versus 0.6 in the female population (p=0.04). Also, severe complications (both infectious and cardiovascular) were mostly found in the male population. SCD-related cardiac complications were observed mainly in the male population: p=0.04, Fisher’s test. Our data support the hypothesis that gender could play a role in determining the clinical course of SCD. The higher morbidity in males is a well-known feature of SCD in adults but this is, to our knowledge, the first study that confirms this finding in a pediatric population. These differences have, in adults, been attributed to hormonal variations found in the two sexes after puberty. In a pediatric population, other factors must be responsible for these differences addressed to in further studies. These findings suggest that gender could be a risk factor of these patients at diagnosis, and possibly guide therapeutic decisions, with the aim of personalizing the therapy.